2012
DOI: 10.1016/j.foodqual.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Using quantitative descriptive analysis and temporal dominance of sensations analysis as complementary methods for profiling commercial blackcurrant squashes

Abstract: a b s t r a c tQuantitative descriptive analysis (QDA) is used to describe the nature and the intensity of sensory properties from a single evaluation of a product, whereas temporal dominance of sensation (TDS) is primarily used to identify dominant sensory properties over time. Previous studies with TDS have focused on model systems, but this is the first study to use a sequential approach, i.e. QDA then TDS in measuring sensory properties of a commercial product category, using the same set of trained assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 28 publications
4
59
0
10
Order By: Relevance
“…Throughout the process the assessor identifies the dominant sensation that are perceived and by comparing responses between the panel we are able to recognize patterns for particular foods by the group of subjects under test. TDS has been applied to a variety of liquid foods and drinks such as water (Teillet, Schlich, Urbano, Cordelle, & Guichard, 2010), espresso coffee (Barron et al, 2012), blackcurrant squash (Ng et al, 2012) wine (Meillon, Urbano, & Schlich, 2009;Sokolowsky & Fischer, 2012) and olive oil (Dinnella, Masi, Zoboli, & Monteleone, 2012). It has also been used to examine semi solid foods like yoghurt (Bruzzone, Ares, & Gimenez, 2013) and salmon-sauce combinations (Paulsen, Naes, Ueland, Rukke, & Hersleth, 2013).…”
Section: Temporal Dominance Of Sensationmentioning
confidence: 99%
“…Throughout the process the assessor identifies the dominant sensation that are perceived and by comparing responses between the panel we are able to recognize patterns for particular foods by the group of subjects under test. TDS has been applied to a variety of liquid foods and drinks such as water (Teillet, Schlich, Urbano, Cordelle, & Guichard, 2010), espresso coffee (Barron et al, 2012), blackcurrant squash (Ng et al, 2012) wine (Meillon, Urbano, & Schlich, 2009;Sokolowsky & Fischer, 2012) and olive oil (Dinnella, Masi, Zoboli, & Monteleone, 2012). It has also been used to examine semi solid foods like yoghurt (Bruzzone, Ares, & Gimenez, 2013) and salmon-sauce combinations (Paulsen, Naes, Ueland, Rukke, & Hersleth, 2013).…”
Section: Temporal Dominance Of Sensationmentioning
confidence: 99%
“…Here, the assessor states which attribute (out of a pre-selected list) is most dominant at different times during consumption (Pineau et al, 2009), noting that the sensation that is most dominant may not be the one that is the most intense. TDS was used alongside QDA profiling in studying the flavour profile of commercial blackcurrant squashes (Ng et al, 2012). The authors concluded that both methods were relevant; QDA intensities did not predict the dominance of sensations, however, TDS alone could not be used to evaluate all attributes and less dominant attributes were still found to be important in product differentiation.…”
Section: Time Dependency Methodsmentioning
confidence: 99%
“…The panelists were trained over 9 h (1.5 h per session, 3 times per week for 2 weeks). The training process followed the method described by Ng et al (2012). The panelists were given several bitter gourd juice formulations and were asked to generate terminology for the juice in terms of sensory attributes (bitter taste, sour taste and viscosity).…”
Section: Descriptive Sensory Analysismentioning
confidence: 99%